MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DESA GUNUNG SARI, KECAMATAN PAMIJAHAN, BOGOR - Ria Kusumaningrum; Fariz Fajar Riyadi; Rully Trihantana (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
This community service aims to Program Access to Sharia Financing for Micro, Small andMedium Enterprises. The subject of this community service is the community of Gunung SariVillage, Pamijahan District, Bogor Regency, West Java Province. In this community service,activities are carried out based on a descriptive method with a qualitative approach. The resultsof this community service are that in addition to providing financing assistance to MSMEs, Islamicbanks must accompany the running of the business and be involved intensely to monitor to ensureMSMEs that receive financial assistance are able to manage finances. well. With this communityservice, it can be concluded that people who work in MSMEs will increase their income andwelfare and of course will directly reduce poverty. engage in business activities that involve formalfinancial institutions.